2000
DOI: 10.1016/s0378-1097(99)00652-7
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory pathways and oxygen toxicity in Phanerochaete chrysosporium

Abstract: Phanerochaete chrysosporium maintained on glucose as the carbon source contained severely impaired mitochondria that were characterised by the loss of both succinate dehydrogenase and cytochrome oxidase activities. These cells maintained a constant value for energy charge using anaerobic metabolism. Cells with these properties express lignin peroxidase when supplied with a pure oxygen atmosphere, which may reflect a response to accumulating reactive oxygen species. Cells maintained on cellulose retained fully … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2003
2003
2003
2003

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
(20 reference statements)
1
2
0
Order By: Relevance
“…Collectively, our results are consistent with recent hypotheses in which oxidative stress conditions affect LIP synthesis in P. chrysosporium (35,36,(44)(45)(46). Rothschild et al (36) suggested that Mn deficiency increases the level of oxygen radicals generated within the cell.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Collectively, our results are consistent with recent hypotheses in which oxidative stress conditions affect LIP synthesis in P. chrysosporium (35,36,(44)(45)(46). Rothschild et al (36) suggested that Mn deficiency increases the level of oxygen radicals generated within the cell.…”
Section: Discussionsupporting
confidence: 93%
“…Rothschild et al (36) suggested that Mn deficiency increases the level of oxygen radicals generated within the cell. Zacchi et al (44)(45)(46) reported a major loss in organization of cellular structure, possibly due to oxygen toxicity, in carbon-limited cultures of P. chrysosporium exposed to an atmosphere of pure O 2, which implies that LIP may be synthesized in response to oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation